Development of android learning media for lubrication system competency in the concentration of light vehicle engineering skills at ma'arif nu 1 ajibarang vocational high school - Pradana, Akbar Surya; Bunyamin; Kurniawan, Adhetya; Khoiron, Ahmad Mustamil (JMEL : Journal of Mechanical Engineering Learning, 2025)
This research aims to develop Android learning media on lubrication system competency. The purpose of this research is to create appropriate learning applications according to experts, determine the effectiveness and efficiency of the media, and determine the response of teachers and students to the media created. This research used the ADDIE development model. This research used a pre-experimental design in the form of a one group pretest-posttest design which was carried out at the Concentration of Light Vehicle Engineering Expertise at SMK Ma'arif NU 1 Ajibarang. The research results showed that Android learning media received a score from media experts of 85.16% in very worthy category and material experts received a score of 88.97% in very worthy category. There is significant differences between the result of pretest and posttest in experiment class (sig. 2-tailed 0.000 < 0.05) and also in control class (sig. 2-tailed 0.000 <0.05).  Android media can improve student learning outcomes in experimental classes with an average percentage increase of 62.15% in quite effective category. Meanwhile, the control class that did not use Android media obtained an average percentage increase of 25.62% in the Ineffective category. There was no time efficiency in this research. The media received a teacher response of 95.45% in very good category and a student response of 77.41% in the "Good" category.